Aqueous stability of leuprolide acetate: effect of temperature, dissolved oxygen, pH and complexation with β-cyclodextrin. (2nd January 2016) - Rahimi, Mehdi; Mobedi, Hamid; Behnamghader, Aliasghar
Abstract: In the present research, the aqueous stability of leuprolide acetate (LA) in phosphate buffered saline (PBS) medium was studied (pH = 2.0–7.4). For this purpose, the effect of temperature, dissolved oxygen and pH on the stability of LA during 35 days was investigated. Results showed that the aqueous stability of LA was higher at low temperatures. Degassing of the PBS medium partially increased the stability of LA at 4 °C, while did not change at 37 °C. The degradation of LA was accelerated at lower pH values. In addition, complexes of LA with different portions of β-cyclodextrin (β-CD) were prepared through freeze-drying procedure and characterized by Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC) analyses. Studying their aqueous stability at various pH values (2.0–7.4) showed LA/β-CD complexes exhibited higher stability when compared with LA at all pH values. The stability of complexes was also improved by increasing the portion of LA/β-CD up to 1/10.